Immunobead RT-PCR: A Sensitive Method for Detection of Circulating Tumor Cells. (January 1997) - Eaton, Michael C.; Hardingham, Jennifer E.; Kotasek, Dusan; Dobrovic, Alexander
Detection of circulating tumor cells and micrometastases in patients with cancer should prove useful in determining prognosis and in planning and monitoring systemic therapies. We have developed immunomagnetic isolation of carcinoma cells followed by reverse transcription polymerase chain reaction (immunobead RT-PCR) as a method for identifying very small numbers of breast cancer cells in blood. The expression of cytokeratin 19 (K19) was used as the marker by which the isolated tumor cells were identified. The immunobead RT-PCR technique allowed detection of one tumor cell per 10 6 leukocytes in whole blood. Immunobead RT-PCR is a highly sensitive method of detecting cancer cells in a hematopoietic environment.